2018
DOI: 10.1111/pde.13407
|View full text |Cite
|
Sign up to set email alerts
|

Doing the math: A simple approach to topical timolol dosing for infantile hemangiomas

Abstract: Topical timolol maleate has recently gained popularity as a treatment for superficial infantile hemangiomas, but calculating a safe dose of timolol can be time consuming, which may limit the medication's use in fast-paced clinical environments. This report offers a simplified calculation of the maximum daily safe dosage as 1 drop of medication per kilogram of body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…We read with interest “Doing the math: A simple approach to topical timolol dosing for infantile hemangiomas.” Dalla Costa et al offered a simple method for calculating a safe maximum daily dose as equivalent to 1 drop of timolol 0.5% gel‐forming solution (GFS) per kilogram of body weight. Our concern is that, according to the proposed weight‐based formula, patients would be eligible to receive more than 2 drops for the majority of treatment duration, because treatment is typically intended to continue through the first year of life.…”
mentioning
confidence: 99%
“…We read with interest “Doing the math: A simple approach to topical timolol dosing for infantile hemangiomas.” Dalla Costa et al offered a simple method for calculating a safe maximum daily dose as equivalent to 1 drop of timolol 0.5% gel‐forming solution (GFS) per kilogram of body weight. Our concern is that, according to the proposed weight‐based formula, patients would be eligible to receive more than 2 drops for the majority of treatment duration, because treatment is typically intended to continue through the first year of life.…”
mentioning
confidence: 99%
“…suggested that a maximum safe dose of 1 drop/kg body weight of 0.5% timolol gel-forming solution can be used for topical application. [ 34 ] However, further studies are necessary before this dosage can be recommended. [ 35 ]…”
Section: Treatment Of Hoimentioning
confidence: 99%